A qualitative exploration of the experiences of living with and being treated for fibromyalgia - Simon C Ashe (Health Psychology Open, 2017)
This study explores the life and treatment experience of people in the United Kingdom with fibromyalgia in order to inform the development of treatments which are both effective and acceptable to users. Qualitative interviews were conducted with 14 participants with interpretative phenomenological analysis used as the theoretical framework and analytical method. The themes identified were as follows: Inauthenticity of fibromyalgia, An Unconventional healthcare experience, Re-creating support networks, Challenging the working identity, Threatening the family dynamic and Fighting, accepting or accommodating? The biopsychosocial impacts of fibromyalgia disrupted the identity, lifestyle, roles and relationships of our participants with such challenges further exacerbated by the contested nature of the illness.